RETRACTED ARTICLE: The effect of n-3/n-6 polyunsaturated fatty acids on acute reflux esophagitis in rats - Ze-Hao Zhuang; Jing-Jing Xie; Jing-Jing Wei; Du-Peng Tang; Li-Yong Yang (Lipids in Health and Disease, 2016)
Abstract Background Polyunsaturated fatty acids (PUFAs) play various roles in inflammation. However, the effect of PUFAs in the development of reflux esophagitis (RE) is unclear. This study is to investigate the potential effect of n-3/n-6 PUFAs on acute RE in rats along with the underlying protective mechanisms. Methods Forty Sprague Dawley rats were randomly divided into four groups (n = 10 in each group). RE model was established by pyloric clip and section ligation. Fish oil- and soybean oil-based fatty emulsion (n-3 and n-6 groups), or normal saline (control and sham operation groups) was injected intraperitoneally 2 h prior to surgery and 24 h postoperatively (2 mL/kg, respectively). The expressions of interleukin (IL)-1β, IL-8, IL-6 and myeloid differentiation primary response gene 88 (MyD88) in esophageal tissues were evaluated by Western blot and immunohistochemistry after 72 h. The malondialdehyde (MDA) and superoxide dismutase (SOD) expression in the esophageal tissues were determined to assess the oxidative stress. Results The mildest macroscopic/microscopic esophagitis was found in the n-3 group (P < 0.05). The expression of IL-1β, IL-8, IL-6 and MyD88 were increased in all RE groups, while the lowest and highest expression were found in n-3 and n-6 group, respectively (P < 0.05). The MDA levels were increased in all groups (P < 0.05), in an ascending trend from n-3, n-6 groups to control group. The lowest and highest SOD levels were found in the control and n-3 group, respectively (P < 0.05). Conclusion n-3 PUFAs may reduce acute RE in rats, which may be due to inhibition of the MyD88-NF-kB pathway and limit oxidative damage.